Literature Study of Learning Outcomes of "Pak Krumun" Cartoon Art Media in Readers' Lives - Agus Wijayanto; Tri Hannanto Saputra; Gregorius Adi Prastiantomo (Poltanesa, 2023)
The communication media tools include the press, print media, film, radio, and television. Communication media has opportunities, challenges, and abilities in providing value to human society. One of the print media studied is cartoons. One of the print media in the form of cartoons is the "Pak Krumun" Cartoon. "Pak Krumun" is a cartoon that is in Utusan Magazine. This research aims to study the influence of "Pak Krumun" cartoon art media on readers' lives. The research methods used are literature study, interviews, and questionnaires. A literature study was conducted to find out about thoughts about cartoons, media, and the Church. Interviews were conducted with readers and Pak Bambang Shakuntala the creator of the "Pak Krumun" cartoon. The questionnaire was given to readers as many as 162 respondents, to find out the learning outcomes obtained from "Pak Krumun" cartoons. "Pak Krumun" cartoon is the work of Bambang Shakuntala who invites people to reflect on their lives. "Pak Krumun" cartoons provide real and concrete themes of people's lives.